The traditional agriculture labor intermediaries as cultural brokers - Sanchez Saldaña, Kim (2016)
In Mexico traditional agriculture labor contractors have had a crucial role in building the large agro-industrial complex. Using empirical evidence as a base, we reflect on the symbolic role these actors play as intermediaries between capital and labor, navigating different cultural spaces, either as representatives or as translators of dissimilar codes. This perspective can serve as a basis to understand labor practices in a rural society but also explain changes associated to quality standards in a contemporary global agribusiness market.